Synchronization of a class of fractional-order neural networks with multiple time delays by comparison principles - Zhang, Weiwei; Wu, Ranchao; Cao, Jinde; Alsaedi, Ahmed; Hayat, Tasawar (Nonlinear Analysis: Modelling and Control, 2017)
This paper studies the synchronization of fractional-order neural networks with multiple time delays. Based on an inequality of fractional-order and comparison principles of linear fractional equation with multiple time delays, some sufficient conditions for synchronization of master-slave systems are obtained. Example and related simulations are given to demonstrate the feasibility of the theoretical results.
Keywords: fractional-order neural networks; comparison principles; multiple time delays; synchronization